MASCULINITY OF HEROINE IN XENA: WARRIOR PRINCESS (1995) AND THE HUNGER GAMES (2012) - Ingga Rosarini; Pepi Siti Paturohmah; Hasbi Assiddiqi (CALL, 2020)
Abstract: This study is aims at revealing the female masculinity or masculine character reflected in the character heroine of Katniss Everdeen and Xena. The characters created are also both heroes mostly born in the adventure genre. Heroine is the female protagonist character. The hero overcomes these opponents because he is strong, brave, resourceful, rational, and determined to succeed, he may receive assistance from wise and benefit being who recognize him for what he is. The words masculine can refer to the property of being biologically male. Inferiority to high culture are derived from, and refer back to, the sexist constructions of femininity and masculinity in the wider society. Researcher look for data relating to the question of the problem, how are the masculinity aspect of heroine described in Xena: Warrior Princess and The Hunger Games Movie. The researcher used comparative method to find differences and similarities of the both character to be used as objects of research with the topic woman characters. From the analysis, it was found that Katniss and Xena had masculinity of heroine. This also shows a striking difference in both character.Keywords:   heroine, masculinity, comparative, film, sexist.